Pertanggungjawaban Hukum Pengelolaan Fasilitas Parkir dalam Perspektif Hukum Perlindungan Konsumen (Studi Kasus Kehilangan Barang di Penyediaan Layanan Penitipan Kendaraan DKI Jakarta) - Randut, Krispianus; Sutrisno , Andri (PT Elaborium Elevasi Indonesia, 2025)
Parking is one of the vehicle storage services used in various places. As one of the vehicle storage services, of course managing parking is one of the business fields. Thus, a legal relationship arises between the parking manager and the vehicle depositor (consumer). The legal relationship between the parking manager and the consumer is based on the goods storage agreement, standard clauses, and the rights and obligations of the parties. To facilitate the implementation of the business, business actors, especially parking managers, use standard clauses. Standard clauses are clauses that are made to facilitate the running of the business without having to make long agreements with many consumers. So that standard clauses are also called unilateral agreements made by business actors only. However, the existence of standard clauses actually harms consumers with regulations that shift the responsibility of business actors to consumers. This can be detrimental to consumers because the form of responsibility of the parking manager as a business actor has been charged to the consumer. Meanwhile, according to the provisions of Article 18 Paragraph (1) of Law No. 8 of 1999 concerning Consumer Protection, it is emphasized that business actors are prohibited from making standard clauses that shift their responsibilities. Therefore, the parking service provider who shifts its responsibility to the consumer is an act that is certainly prohibited by legal norms because it is detrimental to one of the parties. So that consumers can firmly file a lawsuit for the loss or damage of their belongings in the parking lot through civil or criminal lawsuits. For this reason, this study aims to determine the responsibility of parking service providers who also use standard clauses as in the Consumer Protection Law using normative legal research methods.